Tormentic acid, a triterpenoid isolated from the fruits of Chaenomeles speciose, protected indomethacin-induced gastric mucosal lesion via modulating miR-139 and the CXCR4/CXCL12/PLC/PKC/Rho a/MLC pathway - Jun-Yu He; Jie Li; Yuan-Yuan Zhang; Hai-Bo He; Yu-Min He; Dao-Xiang Xu; Xiao Wang; Hao-Yang Wu; Ji-Hong Zhang; Hasan Jahid; Akter Sadia; Hui-Fan Yu; et al. (Taylor & Francis Group, 2023)
AbstractContext Tormentic acid (TA), an effective triterpenoid isolated from Chaenomeles speciosa (Sweet) Nakai (Rosaceae) fruits, exerts an effective treatment for gastric damage.Objective To investigate the gastroprotective effect of TA on indomethacin (IND) damaged GES-1 cells and rats, and explore potential mechanisms.Materials and methods TA concentrations of 1.563-25 µM were used. Cell proliferation, apoptosis and migration were performed using MTT, colony formation, wound healing, migration, Hoechst staining assays. SD rats were divided into control, IND, TA (1, 2 and 4 mg/kg) + IND groups, once a day for 21 continuous days. Twenty-four hours after the last administration, all groups except the control group were given IND (100 mg/kg) by gavage. Gastric juice parameters, gastric ulcer, gastric blood flow (GBF), blood biochemical parameters and cytokine analysis and gastric mucosal histopathology were detected for 2 h and 6 h after IND oral administration. The mRNA and protein expression of miR-139 and the CXCR4/CXCL12/PLC/PKC/Rho A/MLC pathway were analyzed in the IND-damaged GES-1 cells and gastric tissue of rats.Results TA might ameliorate the gastric mucosal injury by accelerating the IND-damaged GES-1 cell proliferation and migration, ameliorating GBF, ulcer area and pathologic changes, the redox system and cytokine levels, the gastric juice parameters, elevating the gastric pH in IND damaged rats; suppressed miR-139 mRNA expression, elevated CXCR4 and CXCL12 mRNA and protein expression, p-PLC, p-PKC, Rho A, MLCK and p-MLC protein expression.Discussion and conclusions TA may have potential use as a clinical drug candidate for gastric mucosal lesion treatment.